Unexpected Benefits in Single Institution Experience With Successful Implementation of a Standardized Perioperative Protocol in Pediatric Thyroidectomy. Issue 3 (14th May 2022) - Cossen, Kristina; Santore, Matthew T.; Prickett, Kara K.; Goudy, Steven L.; Heiss, Kurt F.; Shanker, Kanika; Alazraki, Adina L.; Patterson, Briana C.
Abstract : Introduction: To illustrate how quality improvement can produce unexpected positive outcomes. Methods: We compared a retrospective review of perioperative management and outcomes of baseline 122 pediatric total thyroidectomies to 121 subsequent total thyroidectomies managed by an Electronic Medical Record protocol in a large, free-standing children's healthcare system. Process measures included serum calcium measurement 6−12 hours postoperatively; parathyroid hormone measurement 6 hours postoperatively; preoperative iodine for Graves disease, and postoperative prophylactic calcium carbonate administration. In addition, we completed 4 Plan-Do-Study-Act (PDSA) cycles, focusing on implementation, refinement, usage, education, and postoperative calcitriol administration. The primary outcome included transient hypocalcemia during admission. Results: All perioperative process measures improved over PDSA cycles. Measurement of postoperative serum calcium increased from 42% at baseline to 100%. Measurement of postoperative PTH increased from 11% to 97%. Preoperative iodine administration for Graves disease surgeries improved from 72% to 94%. Postoperative calcium carbonate administration increased from 36% to 100%. There was a trend toward lower rates of severe hypocalcemia during admission over the subsequent PDSA cycles starting at 11.6% and improving to 3.4%. With the regular review of outcomes, surgical volume consolidated among high-volume providers, associated with a decrease in a permanent hypoparathyroid rate of 20.5% at baseline to 10% by the end of monitoring. Conclusions: In standardizing care at 1 large pediatric institution, implementing a focused quality improvement project involving the perioperative management of transient hypocalcemia in total thyroidectomy pediatric patients resulted in additional, unanticipated improvements in patient care.